Pulmoner lenfanjioleiyomiyomatozis: İki olgu nedeniyle - Tanrıverdi, Elif; Gül, Şule; Yaşar, Zehra; Özgül, Mehmet Akif; Günlüoğlu, Mehmet Zeki; Üre, Halide Nur; Çetinkaya, Erdoğan (LookUs Scientific, 2015)
Pulmoner lenfanjioleiyomiyomatozis (LAM) daha çok doğurganlık çağındaki kadınları etkileyen akciğerin nadir kistik hastalığıdır. Progresif dispne, tekrarlayan spontan pnömotoraks, şilotoraks ve bazen tekrarlayan hemoptizi görülebilen semptomlardır. Hastalığın tanısı tipik klinik bulguları olan hastalarda akciğer biyopsisi veya yüksek rezolusyonlu bilgisayarlı tomografisi (YRBT) bulguları ile konabilir. OLGU 1: Otuz iki yaşında bayan hasta tekrarlayan spontan pnömotoraks ve sağ böbrekte anjiyomiyolipom öyküsü olan hastaya videotorakoskopi eşliğinde akciğer biyopsisi yapıldı. Sonucu LAM ile uyumlu idi. Hasta takibe alındı. OLGU 2: Kırk üç yaşında bayan hasta hemoptizi şikâyeti ile kliniğimize başvurdu. Hasta beş yıldır aralıklı olan nefes darlığı ve göğüs ağrısından şikâyetçiydi. YRBT’ de bilateral ince duvarlı hava kistleri izlendi. Torakotomi eşliğinde wedge rezeksiyon uygulandı. Histopatolojik bulguları LAM ile uyumlu olarak raporlandı. Hasta takibe alındı. Sporadik LAM tanısı alan iki farklı klinik özellikteki olgu literatür eşliğinde sunuldu.

Lymphangioleiomyomatosis (LAM) is an uncommon cystic lung disease, primarily affecting women of childbearing age. The clinical presentation is generally progressive dyspnea, recurrent spontaneous pneumothorax, chylous effusion, and occasional hemoptysis. The diagnosis of the disease can be established by lung biopsy or high-resolution computed tomography (HRCT) combined with typical clinical features. CASE 1: A 32-year-old women had recurrent spontaneous pneumothorax and right renal angiomyolipoma. A lung biopsy was performed via videothoracoscopy. The histopathological results were reported as LAM. The patient was followed up. CASE 2: A 43- year-old woman was admitted to our clinic due to hemoptysis after each cough. She complained about chest pain and stridorous breathing for five years. HRCT revealed bilateral thin-walled air cysts. A wedge resection was performed via thoracotomy. The patient was diagnosed with LAM based on the histopathological examination. The patient was monitored. The two rare cases with two different clinical presentations were reported with a literature review.
Pulmonary lymphangioleiomyomatosis: Report of two cases
Keywords: Lenfanjioleiyomiyomatozis; Ayırıcı Tanı; Tedavi; Sirolimus; Lymphangioleiomyomatosis; Differential Diagnosis; Treatment